Prevention of hearing handicap - Catlin, Francis I (Journal of All India Institute of Speech and Hearing)
Many problems in audiology are not solved because superficial appearances are taken at face value, and little attempt is made to ferret out the principles which lie beneath. The prevention of hearing handicap is such a problem.